2004
DOI: 10.1128/jvi.78.3.1513-1524.2004
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Host Cell Interactions during Hepatitis C Virus RNA Replication: Impact of Polyprotein Expression on the Cellular Transcriptome and Cell Cycle Association with Viral RNA Synthesis

Abstract: Hepatitis C is the most common cause of clinically significant liver disease in the United States. Although acute infection with hepatitis C virus (HCV) is usually subclinical, persistent infection develops in up to 80% of initially infected patients (2). The majority of persistently infected individuals develop evidence of chronic liver injury and are at risk for progressive hepatic fibrosis leading to cirrhosis and ultimately death due to liver failure or hepatocellular carcinoma. Approximately 10,000 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 65 publications
(88 reference statements)
2
78
0
Order By: Relevance
“…We have shown that HCV RNA synthesis is stimulated during the S phase of the cell cycle (13). Moreover, compared with capdependent translation, the cap-independent translation of HCV RNA is enhanced in actively growing cells and reduced in resting cells (29).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have shown that HCV RNA synthesis is stimulated during the S phase of the cell cycle (13). Moreover, compared with capdependent translation, the cap-independent translation of HCV RNA is enhanced in actively growing cells and reduced in resting cells (29).…”
Section: Discussionmentioning
confidence: 98%
“…We studied two independent, Huh7 hepatoma cell lines, NNeo͞ C-5B clones 2-3 and 3, both of which contain replicating genome-length RNA expressing all of the proteins of the HCV-N strain (12). We compared the abundance of Rb in these cell lines with that in their progeny, designated 2-3c and 3c, respectively, in which HCV RNA had been eliminated by prior treatment with IFN-␣2b (13). The abundance of Rb in each of the HCV RNA-containing cell lines was reduced compared with that in the cognate-cured cell line (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the abundance of ectopically expressed TRIF-Flag in Huh7 2-3 cells, which express NS3͞4A from a replicating genome-length RNA, and in clonally related 2-3c cells from which the viral RNA had been eliminated by prior IFN-␣2b treatment (29). Quantitative immunoblot analysis indicated that TRIF-Flag abundance was reduced Ϸ50% in the 2-3 cells compared with the cured 2-3c cells (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Huh7-HP, Huh7-A7, and Huh7-K2040 are Huh7 cells that harbor culture-adapted variants of the Con1 HCV (genotype 1b) subgenomic replicon RNA and have been described in detail (3,6,9). Huh7 2-3 and Huh7 2-3c are Huh7-derived cell lines that harbor the full-length self-replicating HCV genome (derived from the HCV-N strain, genotype 1b) and their IFN-cured counterparts, respectively (3,10,11). UNS3͞4A (clone 24) are osteosarcoma cells that conditionally express an HCV 1a NS3͞4A construct under control of a tetracycline-regulated (tet-off) promoter (a gift from D. Moradpour, University of Lausanne, Lausanne, Switzerland).…”
Section: Methodsmentioning
confidence: 99%